If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -7a = -6a + 8 Reorder the terms: 8 + -7a = 8 + -6a Add '-8' to each side of the equation. 8 + -8 + -7a = 8 + -8 + -6a Combine like terms: 8 + -8 = 0 0 + -7a = 8 + -8 + -6a -7a = 8 + -8 + -6a Combine like terms: 8 + -8 = 0 -7a = 0 + -6a -7a = -6a Solving -7a = -6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6a' to each side of the equation. -7a + 6a = -6a + 6a Combine like terms: -7a + 6a = -1a -1a = -6a + 6a Combine like terms: -6a + 6a = 0 -1a = 0 Divide each side by '-1'. a = 0 Simplifying a = 0
| 2x-3x+x= | | 6x-14x+16=46 | | -4a^7+8a^6-2a^5= | | 4x^2+9=12s | | 5m+6n= | | u+5=7 | | F=-3x+21 | | 47x=8 | | 15+7=7 | | 17x-8x-9=36 | | 6x+4+2x=34-2x | | y(x-6)+2(x-6)= | | X+X^3=200 | | (7x+3)*(2x-5)= | | -4+a=-12 | | 15y+6=23 | | 7x+3-2x-5= | | 7x+3+2x-5= | | 10(3n+8)= | | N-7=55 | | 9+5=19 | | 5(2x-4)-4(3x-2)-8x=1 | | 6x+19+4x-11=72+2x+16 | | (x-111)+x+(x-111)+x=3774 | | 2x^6-4x^5-24x^4-94x^3+28x^2=0-20x+9 | | 3(5x-8)-2(x-5)=x+2 | | -8m+6-2m=9(3m+4)+5m | | x^4+6*x^2+25=0 | | 3x+5=345 | | s^4+4s^3+9s^2+10s-6=0 | | x+15=36-x | | 3a-10d=0 |